"We Can Help the People Who Can Make a Difference": Motivations, Goals, and Outcomes in Volunteer Water Quality Monitoring. Issue 2 (3rd April 2017) - McCauley, Jaime
ABSTRACT: This research examines motivations and goals of individuals participating in volunteer water quality monitoring programs and the ways in which volunteer collected data are used as well as the potential impact on environmental governance. Findings indicate that participants are primarily motivated to protect water as a natural resource and seek to do so by sharing citizen-collected data with government environmental management agencies. The impact of monitoring programs is uniformly positive for raising citizen awareness about water quality issues and building data sets but is uneven when it comes to policy influence. The experience of volunteer water quality monitors and the outcomes of their work are shaped by social contexts of scientization and neoliberalism. These contexts facilitate openings for citizen participation in data collection and environmental governance but also create limits on the extent to which volunteer data can be used for policy-making.